2016
DOI: 10.1111/cote.12241
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of lac dye by the red marine alga Gracilaria tenuistipitata: biosorption kinetics, isotherms, and thermodynamic parameters

Abstract: The hypothesis that the dried, ground biomass of the red marine alga Gracilaria tenuistipitata could be used for the efficient removal of lac dye from aqueous solution was assessed in this work. The effects of parameters such as initial pH, biosorbent dosage, contact time, initial dye concentration, and temperature on the biosorption capacity of the dye were investigated. Equilibrium data were analysed using Langmuir, Freundlich, and Temkin isotherm models, and the Freundlich model provided the highest coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Temperature affects the biosorption efficiency of algae species for each metal ion [85,97,98]. Although the constants for metal-ligand complex formation are predominantly temperature-dependent, some studies have suggested that an increase in algal culture temperatures is responsible for an increase in metal-ion biosorption, without considering the changes in the formation constants [99,100]. The percentage of Zn +2 and Fe +3 ions that were removed from DAP and AAC of U. lactuca and C. officinalis increased as the temperature increased, indicating an endothermic adsorption process, which is a positive effect when considering the use of these algae in the environment, as well as their potential conservation and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature affects the biosorption efficiency of algae species for each metal ion [85,97,98]. Although the constants for metal-ligand complex formation are predominantly temperature-dependent, some studies have suggested that an increase in algal culture temperatures is responsible for an increase in metal-ion biosorption, without considering the changes in the formation constants [99,100]. The percentage of Zn +2 and Fe +3 ions that were removed from DAP and AAC of U. lactuca and C. officinalis increased as the temperature increased, indicating an endothermic adsorption process, which is a positive effect when considering the use of these algae in the environment, as well as their potential conservation and sustainability.…”
Section: Discussionmentioning
confidence: 99%